Adapting SAM3 for 3D fruit counting with cross-view contrastive learning and Hough voting - Kai Zhao; Chenchen Kang; Suzy Rogiers; Oula Ghannoum; Yi Guo (Computers and Electronics in Agriculture, 2026)

Auxin-mediated regulation and functional adaptation of leaf veins under heat stress - Afroz Naznin; Yuanyuan Wang; Jing He; Md Mazadul Islam; Asad Abbas; Jay Bose; Oula Ghannoum; Zhong-Hua Chen (Journal of Plant Physiology, 2026)

Advancements in Saffron Cultivation: Soilless Farming Techniques and IoT Integration - Munjid Maryam; Rohitashw Kumar; Dharmappa Hagare; Oula Ghannoum; Shirin Moradi; Bashir Ellahi; Prasanth; Safeena S A; Shakeel Ahmad Mir (Next Research, 2025)

Key physiological traits for drought tolerance identified through phenotyping a large set of slicing cucumber (Cucumis sativus L.) genotypes under field and water-stress conditions - Anjan Das; A. D. Munshi; Dhandapani Raju; Sudhir Kumar; Dharmendara Singh; Akshay Talukdar; Dhananjay Hongal; Mir Asif Iquebal; Sandeep Kumar; R. C. Bhattacharya; Pragya Ranjan; Oula Ghannoum; et al. (Genetic Resources and Crop Evolution, 2024)

Machine vision based plant height estimation for protected crop facilities - Namal Jayasuriya; Yi Guo; Wen Hu; Oula Ghannoum (Computers and Electronics in Agriculture, 2024)

Adaptation of plants to a high CO2 and high-temperature world - Wataru Yamori; Oula Ghannoum (Plant Molecular Biology, 2022)

Moderate heat stress prevented the observed biomass and yield stimulation caused by elevated CO2 in two well-watered wheat cultivars - Sachin G. Chavan; Remko A. Duursma; Michael Tausz; Oula Ghannoum (Plant Molecular Biology, 2022)
Key message Heat stress (HS) under well-watered conditions was not detrimental to leaf photosynthesis or yield but modified the elevated CO 2 response of photosynthesis and yield in two contrasting wheat cultivars. Abstract Climate change is increasing the frequency of extreme events such as heat waves, adversely affecting crop productivity. While positive impacts of elevated carbon dioxide (eCO 2 ) on crop productivity are evident, the interactive effects of eCO 2 and environmental stresses are still unclear. To investigate the interactive effects of elevated CO 2 and heat stress (HS), we grew two contrasting wheat cultivars, early-maturing Scout and high-tillering Yitpi, under non-limiting water and nutrients at ambient (aCO 2 , 450 ppm) or elevated (eCO 2 , 650 ppm) CO 2 and 22 °C in the glasshouse. Plants were exposed to two 3-day HS cycles at the vegetative (38.1 °C) and/or flowering (33.5 °C) stage. At aCO 2 , both wheat cultivars showed similar responses of photosynthesis and mesophyll conductance to temperature and produced similar grain yield. Relative to aCO 2 , eCO 2 enhanced photosynthesis rate and reduced stomatal conductance and maximal carboxylation rate ( V cmax ). During HS, high temperature stimulated photosynthesis at eCO 2 in both cultivars, while eCO 2 stimulated photosynthesis in Scout. Electron transport rate ( J max ) was unaffected by any treatment. eCO 2 equally enhanced biomass and grain yield of both cultivars in control, but not HS, plants. HS reduced biomass and yield of Scout at eCO 2 . Yitpi, the cultivar with higher grain nitrogen, underwent a trade-off between grain yield and nitrogen. In conclusion, eCO 2 improved photosynthesis of control and HS wheat, and improved biomass and grain yield of control plants only. Under well-watered conditions, HS was not detrimental to photosynthesis or growth but precluded a yield response to eCO 2 .

Mehler reaction plays a role in C3 and C4 photosynthesis under shade and low CO2 - Julius Ver Sagun; Murray R. Badger; Wah Soon Chow; Oula Ghannoum (Photosynthesis Research, 2021)

Cyclic electron flow and light partitioning between the two photosystems in leaves of plants with different functional types - Julius Ver Sagun; Murray R. Badger; Wah Soon Chow; Oula Ghannoum (Photosynthesis Research, 2019)
Cyclic electron flow (CEF) around photosystem I (PSI) is essential for generating additional ATP and enhancing efficient photosynthesis. Accurate estimation of CEF requires knowledge of the fractions of absorbed light by PSI ( f I ) and PSII ( f II ), which are only known for a few model species such as spinach. No measures of f I are available for C 4 grasses under different irradiances. We developed a new method to estimate (1) f II in vivo by concurrently measuring linear electron flux through both photosystems $$\left( {{\text{LEF}}_{{{\text{O}}_{ 2} }} } \right)$$ LEF O 2 in leaf using membrane inlet mass spectrometry (MIMS) and total electron flux through PSII (ETR2) using chlorophyll fluorescence by a Dual-PAM at low light and (2) CEF as ETR1— $${\text{LEF}}_{{{\text{O}}_{ 2} }}$$ LEF O 2 . For a C 3 grass, f I was 0.5 and 0.4 under control (high light) and shade conditions, respectively. C 4 species belonging to NADP-ME and NAD-ME subtypes had f I of 0.6 and PCK subtype had 0.5 under control. All shade-grown C 4 species had f I of 0.6 except for NADP-ME grass which had 0.7. It was also observed that f I ranged between 0.3 and 0.5 for gymnosperm, liverwort and fern species. CEF increased with irradiance and was induced at lower irradiances in C 4 grasses and fern relative to other species. CEF was greater in shade-grown plants relative to control plants except for C 4 NADP-ME species. Our study reveals a range of CEF and f I values in different plant functional groups. This variation must be taken into account for improved photosynthetic calculations and modelling.

Lower photorespiration in elevated CO 2 reduces leaf N concentrations in mature Eucalyptus trees in the field - Agnieszka Wujeska‐Klause; Kristine Y. Crous; Oula Ghannoum; David S. Ellsworth (Global Change Biology, 2019)
Rising atmospheric CO 2 concentrations is expected to stimulate photosynthesis and carbohydrate production, while inhibiting photorespiration. By contrast, nitrogen (N) concentrations in leaves generally tend to decline under elevated CO 2 (eCO 2 ), which may reduce the magnitude of photosynthetic enhancement. We tested two hypotheses as to why leaf N is reduced under eCO 2 : (a) A “dilution effect” caused by increased concentration of leaf carbohydrates; and (b) inhibited nitrate assimilation caused by reduced supply of reductant from photorespiration under eCO 2 . This second hypothesis is fully tested in the field for the first time here, using tall trees of a mature Eucalyptus forest exposed to Free‐Air CO 2 Enrichment (EucFACE) for five years. Fully expanded young and mature leaves were both measured for net photosynthesis, photorespiration, total leaf N, nitrate ( ) concentrations, carbohydrates and reductase activity to test these hypotheses. Foliar N concentrations declined by 8% under eCO 2 in new leaves, while the fraction and total carbohydrate concentrations remained unchanged by CO 2 treatment for either new or mature leaves. Photorespiration decreased 31% under eCO 2 supplying less reductant, and in situ reductase activity was concurrently reduced (−34%) in eCO 2 , especially in new leaves during summer periods. Hence, assimilation was inhibited in leaves of E. tereticornis and the evidence did not support a significant dilution effect as a contributor to the observed reductions in leaf N concentration. This finding suggests that the reduction of reductase activity due to lower photorespiration in eCO 2 can contribute to understanding how eCO 2 ‐induced photosynthetic enhancement may be lower than previously expected. We suggest that large‐scale vegetation models simulating effects of eCO 2 on N biogeochemistry include both mechanisms, especially where is major N source to the dominant vegetation and where leaf flushing and emergence occur in temperatures that promote high photorespiration rates.

Investigating the NAD-ME biochemical pathway within C4 grasses using transcript and amino acid variation in C4 photosynthetic genes - Alexander Watson-Lazowski; Alexie Papanicolaou; Robert Sharwood; Oula Ghannoum (Photosynthesis Research, 2018)

Photosynthetic capacity and leaf nitrogen decline along a controlled climate gradient in provenances of two widely distributed Eucalyptus species - Kristine Y. Crous; John E. Drake; Michael J. Aspinwall; Robert E. Sharwood; Mark G. Tjoelker; Oula Ghannoum (Global Change Biology, 2018)
Climate is an important factor limiting tree distributions and adaptation to different thermal environments may influence how tree populations respond to climate warming. Given the current rate of warming, it has been hypothesized that tree populations in warmer, more thermally stable climates may have limited capacity to respond physiologically to warming compared to populations from cooler, more seasonal climates. We determined in a controlled environment how several provenances of widely distributed Eucalyptus tereticornis and E. grandis adjusted their photosynthetic capacity to +3.5°C warming along their native distribution range (~16–38°S) and whether climate of seed origin of the provenances influenced their response to different growth temperatures. We also tested how temperature optima ( T opt ) of photosynthesis and J max responded to higher growth temperatures. Our results showed increased photosynthesis rates at a standardized temperature with warming in temperate provenances, while rates in tropical provenances were reduced by about 40% compared to their temperate counterparts. Temperature optima of photosynthesis increased as provenances were exposed to warmer growth temperatures. Both species had ~30% reduced photosynthetic capacity in tropical and subtropical provenances related to reduced leaf nitrogen and leaf Rubisco content compared to temperate provenances. Tropical provenances operated closer to their thermal optimum and came within 3% of the T opt of J max during the daily temperature maxima. Hence, further warming may negatively affect C uptake and tree growth in warmer climates, whereas eucalypts in cooler climates may benefit from moderate warming.

Water availability affects seasonal CO 2 ‐induced photosynthetic enhancement in herbaceous species in a periodically dry woodland - Varsha S. Pathare; Kristine Y. Crous; Julia Cooke; Danielle Creek; Oula Ghannoum; David S. Ellsworth (Global Change Biology, 2017)
Elevated atmospheric CO 2 ( eCO 2 ) is expected to reduce the impacts of drought and increase photosynthetic rates via two key mechanisms: first, through decreased stomatal conductance (g s ) and increased soil water content ( V SWC ) and second, through increased leaf internal CO 2 (C i ) and decreased stomatal limitations (S lim ). It is unclear if such findings from temperate grassland studies similarly pertain to warmer ecosystems with periodic water deficits. We tested these mechanisms in three important C 3 herbaceous species in a periodically dry Eucalyptus woodland and investigated how eCO 2 ‐induced photosynthetic enhancement varied with seasonal water availability, over a 3 year period. Leaf photosynthesis increased by 10%–50% with a 150 μmol mol −1 increase in atmospheric CO 2 across seasons. This eCO 2 ‐induced increase in photosynthesis was a function of seasonal water availability, given by recent precipitation and mean daily V SWC . The highest photosynthetic enhancement by eCO 2 (>30%) was observed during the most water‐limited period, for example, with V SWC eCO 2 there was neither a significant decrease in g s in the three herbaceous species, nor increases in V SWC , indicating no “water‐savings effect” of eCO 2 . Periods of low V SWC showed lower g s (less than ≈ 0.12 mol m −2 s −1 ), higher relative S lim (>30%) and decreased C i under the ambient CO 2 concentration ( aCO 2 ), with leaf photosynthesis strongly carboxylation‐limited. The alleviation of S lim by eCO 2 was facilitated by increasing C i , thus yielding a larger photosynthetic enhancement during dry periods. We demonstrated that water availability, but not eCO 2 , controls g s and hence the magnitude of photosynthetic enhancement in the understory herbaceous plants. Thus, eCO 2 has the potential to alter vegetation functioning in a periodically dry woodland understory through changes in stomatal limitation to photosynthesis, not by the “water‐savings effect” usually invoked in grasslands.

A common thermal niche among geographically diverse populations of the widely distributed tree species Eucalyptus tereticornis : No evidence for adaptation to climate‐of‐origin - John E. Drake; Angelica Vårhammar; Dushan Kumarathunge; Belinda E. Medlyn; Sebastian Pfautsch; Peter B. Reich; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2017)
Impacts of climate warming depend on the degree to which plants are constrained by adaptation to their climate‐of‐origin or exhibit broad climatic suitability. We grew cool‐origin, central and warm‐origin provenances of Eucalyptus tereticornis in an array of common temperature environments from 18 to 35.5°C to determine if this widely distributed tree species consists of geographically contrasting provenances with differentiated and narrow thermal niches, or if provenances share a common thermal niche. The temperature responses of photosynthesis, respiration, and growth were equivalent across the three provenances, reflecting a common thermal niche despite a 2,200 km geographic distance and 13°C difference in mean annual temperature at seed origin. The temperature dependence of growth was primarily mediated by changes in leaf area per unit plant mass, photosynthesis, and whole‐plant respiration. Thermal acclimation of leaf, stem, and root respiration moderated the increase in respiration with temperature, but acclimation was constrained at high temperatures. We conclude that this species consists of provenances that are not differentiated in their thermal responses, thus rejecting our hypothesis of adaptation to climate‐of‐origin and suggesting a shared thermal niche. In addition, growth declines with warming above the temperature optima were driven by reductions in whole‐plant leaf area and increased respiratory carbon losses. The impacts of climate warming will nonetheless vary across the geographic range of this and other such species, depending primarily on each provenance's climate position on the temperature response curves for photosynthesis, respiration, and growth.

The capacity to cope with climate warming declines from temperate to tropical latitudes in two widely distributed Eucalyptus species - John E. Drake; Michael J. Aspinwall; Sebastian Pfautsch; Paul D. Rymer; Peter B. Reich; Renee A. Smith; Kristine Y. Crous; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2015)
As rapid climate warming creates a mismatch between forest trees and their home environment, the ability of trees to cope with warming depends on their capacity to physiologically adjust to higher temperatures. In widespread species, individual trees in cooler home climates are hypothesized to more successfully acclimate to warming than their counterparts in warmer climates that may approach thermal limits. We tested this prediction with a climate‐shift experiment in widely distributed Eucalyptus tereticornis and E. grandis using provenances originating along a ~2500 km latitudinal transect (15.5–38.0°S) in eastern Australia. We grew 21 provenances in conditions approximating summer temperatures at seed origin and warmed temperatures (+3.5 °C) using a series of climate‐controlled glasshouse bays. The effects of +3.5 °C warming strongly depended on home climate. Cool‐origin provenances responded to warming through an increase in photosynthetic capacity and total leaf area, leading to enhanced growth of 20–60%. Warm‐origin provenances, however, responded to warming through a reduction in photosynthetic capacity and total leaf area, leading to reduced growth of approximately 10%. These results suggest that there is predictable intraspecific variation in the capacity of trees to respond to warming; cool‐origin taxa are likely to benefit from warming, while warm‐origin taxa may be negatively affected.

Exposure to preindustrial, current and future atmospheric CO 2 and temperature differentially affects growth and photosynthesis in Eucalyptus - OULA GHANNOUM; NATHAN G. PHILLIPS; JANN P. CONROY; RENEE A. SMITH; RENEE D. ATTARD; ROSLYN WOODFIELD; BARRY A. LOGAN; JAMES D. LEWIS; DAVID T. TISSUE (Global Change Biology, 2010)
To investigate if Eucalyptus species have responded to industrial‐age climate change, and how they may respond to a future climate, we measured growth and physiology of fast‐ ( E. saligna ) and slow‐growing ( E. sideroxylon ) seedlings exposed to preindustrial (290), current (400) or projected (650 μL L −1 ) CO 2 concentration ([CO 2 ]) and to current or projected (current +4 °C) temperature. To evaluate maximum potential treatment responses, plants were grown with nonlimiting soil moisture. We found that: (1) E. sideroxylon responded more strongly to elevated [CO 2 ] than to elevated temperature, while E. saligna responded similarly to elevated [CO 2 ] and elevated temperature; (2) the transition from preindustrial to current [CO 2 ] did not enhance eucalypt plant growth under ambient temperature, despite enhancing photosynthesis; (3) the transition from current to future [CO 2 ] stimulated both photosynthesis and growth of eucalypts, independent of temperature; and (4) warming enhanced eucalypt growth, independent of future [CO 2 ], despite not affecting photosynthesis. These results suggest large potential carbon sequestration by eucalypts in a future world, and highlight the need to evaluate how future water availability may affect such responses.